With homage to Petko Staynov - a collection of piano pieces on themes by the composer - Stoyancheva, Jasmina (Young Scientific Music and Dance Forum : Conference with international participation, 2020)
The report examines the relation „modern music – Bulgarian composer classics“. Petko Staynov’s piano pieces collection is related to the pianist contest „Vivapiano“, which is intended for non-professional pianists (founded by the pianist prof. Daniela Dikova, PhD). Seventeen authors’ piano works and pieces on musical themes from the symphonic suite „Thracian Dance“ by Petko Staynov are included in the edition. The variety of compositional approaches will be traced, and the piece „Ruchenitsa (full version)“ by Gheorghi Arnaoudov is analyzed. The author presents his composition in another „short version“. He also creates „Two easy pieces on themes from „Paydushko“, and 3 easy pieces, composed for 4 hands on songs by Petko Staynov. The formulation of the topic and the related materials – text, publications, armticles, etc. are part of my research work related to my dissertation. It focuses on the integral research, analysis and completion of the electronic archive of the composer Petko Staynov.